2019
DOI: 10.3322/caac.21565
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment and survivorship statistics, 2019

Abstract: effects are also briefly described. More than 16.9 million Americans (8.1 million males and 8.8 million females) with a history of cancer were alive on January 1, 2019; this number is projected to reach more than 22.1 million by January 1, 2030 based on the growth and aging of the population alone. The 3 most prevalent cancers in 2019 are prostate (3,650,030), colon and rectum (776,120), and melanoma of the skin (684,470) among males, and breast (3,861,520), uterine corpus (807,860), and colon and rectum (768,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
2,656
2
36

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 3,616 publications
(2,855 citation statements)
references
References 164 publications
10
2,656
2
36
Order By: Relevance
“…As of January 1, 2016, there were estimated to be over 15.5 million cancer survivors in the USA [1]. The number of survivors will increase significantly as a result of ageing of the population, increased cancer detection and improved treatments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As of January 1, 2016, there were estimated to be over 15.5 million cancer survivors in the USA [1]. The number of survivors will increase significantly as a result of ageing of the population, increased cancer detection and improved treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The number of survivors will increase significantly as a result of ageing of the population, increased cancer detection and improved treatments. By January 1, 2026, the number of survivors in the USA is estimated to exceed 20 million [1]. The most prevalent groups are survivors of breast, prostate and colorectal cancer, melanoma and lymphoma [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Authors contributed equally to this work.2 However, its roles in nasopharyngeal carcinoma (NPC) are poorly understood.Although several studies have shown that FOXC2 promotes the progression of NPC, the underlying molecular mechanism remains largely unknown. Here, we have shown that FOXC2 interacted with YAP and TEAD, and activated YAP signaling.…”
mentioning
confidence: 99%